Synthesis, structural features and gas-sensing properties of highly defective titanium dioxide - Boboriko, Natalia E.; Sviridov, Dmitry V. (Journal of the Belarusian State University. Chemistry, 2020)
By the chemical reduction of sol-gel synthesized TiO2, nanoscale black titanium dioxide in anatase modification, characterized by the presence of large quantity of oxygen vacancies and pronounced extrinsic absorption, was obtained. Semiconducting chemical gas sensors on the basis of the obtained highly defective titanium dioxide demonstrate high output value towards ethanol vapor. The output value significantly increases additionally under actinic radiation conditions.
Keywords: black titanium dioxide; anatase; oxygen vacancies; gas sensing properties; ethanol